Detection of polycyclic aromatic hydrocarbons by surface enhanced Raman scattering on colloidal silver substrates - Dzhanabekova, R.Kh.; Kim, M.S.; Ibrayev, N.Kh. (KSU Publ., 2020)
The present work reports on the possibility of polycyclic aromatic hydrocarbons (PAHs) detection by surface enhanced Raman scattering (SERS) on substrates coated with colloidal silver stabilized with cetyltrimethylammonium bromide (CTAB). It was shown that cetyltrimethylammonium bromide acts not only as a stabilizer of metal nanoparticles, but also as modifying agent that promotes the concentration of hydrophobic PAH molecules near the amplified electromagnetic field of plasmon silver nanoparticles. Anthracene and pyrene were used as model analytes. To determine the sensitivity of the prepared SERS active coating, ethanol solutions of the analyzed substances with concentrations in the range of 2·10-4 — 10-6 mol/L were used. The lowest concentrations of solutions for which anthracene and pyrene are found on the tested substrates were equal to 2.5·10-6 M and 5·10-5 M, respectively. These results indicate that substrates are more sensitive to anthracene than to pyrene. The work also shows that various PAH molecules can be detected by characteristic peaks in a complex mixture without preliminary separation of the components.
Коллоидты күміс төсеніштерінде полициклді хош иісті көмірсутектерді беті-күшейтілген комбинациондық шашырау əдісімен анықтау
Определение полициклических ароматических углеводородов методом поверхностно-усиленного комбинационного
Keywords: surface-enhanced Raman scattering; polycyclic aromatic hydrocarbons; anthracene; pyrene; silver nanoparticles; cetyltrimethylammonium bromide; SERS sensor; plasmon particles